Of Micro Sharia People's Business Credit (KUR) Financing Products At Bank Syariah Indonesia Sub-Branch Office Bulukumba Samratulangi - Musayyin Abdullah; Mukhaer Pakkanna (Cita konsultindo, 2025)
This research aims to find out more deeply about Sharia Micro KUR Financing Products and find out how BSI KCP Bulukumba minimizes the risks faced.The methodology used in this research is descriptive qualitative, utilizing interviews, observation, and documentation to gather information from BSI employees. The results showed that KUR Mikro Syariah has played an important role in facilitating access to financing for micro enterprises, thus contributing to their growth and sustainability. However, challenges such debtor default have been identified as significant obstacles. To mitigate these risks, BSI has implemented risk management strategies that are compliant with sharia principles, including regular monitoring. The study reached the conclusion that while KUR Mikro Syariah has the potential to boost Bulukumba's economy, continuous improvements in supervision and support mechanisms are important to maximize the impact it can have on the local economy.